PATTERNS OF SPERMATOZOA MOVEMENT IN THE ALPACA (VICUGNAPACOS): EX SITU OBSERVATIONS - Pacheco C., Joel (2011)
The sperm hyperactivation is a step of the spermatozoa capacitation and consists ona change in the pattern of movements, the variation of the angle of the head, and thelongitude and width of the movement of the tail. The objective of the present study wasto determine the difference in movement patterns of spermatozoa and the frequency ofhyperactive spermatozoa in the oviduct according to the time after mating. The recoveryof the spermatozoa in five alpacas was done after 16, 20, 24, 28 and 32 hours post mating.Sperms were evaluated according to the pattern of movement. The frequency ofhyperactive spermatozoa increased until 28 hours post copula (71.4%).